The jumping lynx spider Oxyopes salticus Hentz, 1845 and its Neotropical relatives (Araneae: Oxyopidae) - Santos, Adalberto J. (Zootaxa, 2017)
The spider genus Oxyopes Latreille occurs throughout the world, but is insufficiently known in South America and the Caribbean. In this study, three apparently related species of this genus are reported from the region. Oxyopes salticus Hentz, 1845 is redescribed and illustrated, and extreme variation in colour pattern and in female genitalia is reported within this species. Oxyopes m-fasciatus Piza, 1938 and Oxyopes nigrolineatus Mello-Leitão, 1941 are both considered junior synonyms of O. salticus. The material examined in this study, together with information from the literature, show this species is widely distributed throughout the continental Americas and the Caribbean. Oxyopes crewi Bryant, 1948 is redescribed and illustrated, and its geographic distribution is extended to Bahamas, Cuba, Dominican Republic, Jamaica, and Saint Kitts. A new species, Oxyopes incantatus sp. nov., is described and illustrated for the first time based on specimens from the Galápagos Islands.